2021
DOI: 10.1001/jamainternmed.2021.3836
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cycling With All-Cause and Cardiovascular Disease Mortality Among Persons With Diabetes

Abstract: IMPORTANCEPremature death from all causes and cardiovascular disease (CVD) causes is higher among persons with diabetes.OBJECTIVE To investigate the association between time spent cycling and all-cause and CVD mortality among persons with diabetes, as well as to evaluate the association between change in time spent cycling and risk of all-cause and CVD mortality. DESIGN, SETTING, AND PARTICIPANTSThis prospective cohort study included 7459 adults with diabetes from the European Prospective Investigation into Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…We agree with Burtscher and colleagues that participants with diabetes who engage in cycling may be healthier than those with diabetes who do not. This may confound the relationship between cycling and mortality.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…We agree with Burtscher and colleagues that participants with diabetes who engage in cycling may be healthier than those with diabetes who do not. This may confound the relationship between cycling and mortality.…”
supporting
confidence: 81%
“…Along with strong experimental evidence showing that cycling elicits health benefits similar to structured exercise in people with overweight or obesity, we have confidence that cycling could contribute directly to a decreased risk of premature mortality. However, as we acknowledge in our article, known and unknown confounding cannot be ruled out in this cohort study …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor We read with great interest the Original Investigation recently published in this journal by Dr Ried-Larsen and colleagues . The authors reported decreased mortality from all causes and from cardiovascular diseases associated with cycling in adults with diabetes.…”
mentioning
confidence: 95%
“…Bicycling is associated with several health benefits, including reduced all-cause mortality, cancer, and cardiovascular risk. [1][2][3][4] In addition, a shift from motorized travel to active transport such as bicycling, may reduce greenhouse gas emissions. 5 Despite the benefits, bicycle riders are at risk of injuries due to accidents.…”
Section: Introductionmentioning
confidence: 99%